Evaluation of antimicrobial and antiadherent properties of copper sulphate (Cu2SO4) and monoterpenes against Lactobacillus acidophilus and Streptococcus mutans - Pérez-Palma, Leticia Deudovika; Andrade-Ochoa, Sergio; Levario-Gómez, Anahí; Cantú-Solis, Eduardo; Sánchez-Aldana, Daniela; Nevárez-Moorillón, Guadalupe Virginia; Loya-Loya, Martha Elena (Acta Universitaria, 2019)
The aim of this study was to evaluate the antimicrobial activity and antibiofilm properties of copper sulfate (Cu2SO4) in association with terpenes against L. acidophilus and S. mutans strains. First, the minimum inhibitory concentration (MIC) was determined using resazurin as indicator of cellular metabolism. Synergic or antagonic effects were determined by the checkerboard method, and the inhibition of biofilm formation was determined by reduction on bacterial count. Results demonstrated that Cu2SO4 had a better antimicrobial activity than the terpenes studied, with MIC of 50 Î¼g/mL and 100 Î¼g/mL against L. acidophilus and S. mutans, respectively. Regardless of this antimicrobial activity, Cu2SO4 alone lacks good inhibition properties in biofilm formation. A synergistic effect was observed with geraniol for both reduction in biofilm formation and antimicrobial activity. The present study highlights the antimicrobial activity of Cu2SO4 against microorganisms related to caries development, and that its combination with terpene compounds can be an effective alternative for the control of these etiological agents.